2021
DOI: 10.1016/j.bios.2021.113122
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 S1 NanoBiT: A nanoluciferase complementation-based biosensor to rapidly probe SARS-CoV-2 receptor recognition

Abstract: As the COVID-19 pandemic continues, there is an imminent need for rapid diagnostic tools and effective antivirals targeting SARS-CoV-2. We have developed a novel bioluminescence-based biosensor to probe a key host-virus interaction during viral entry: the binding of SARS-CoV-2 viral spike (S) protein to its receptor, angiotensin-converting enzyme 2 (ACE2). Derived from Nanoluciferase binary technology (NanoBiT), the biosensor is composed of Nanoluciferase split into two complementary subunits, Large BiT and Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Rather than examining RBD–ACE2 binding, this biosensor specifically interrogates the spike S1 domain and ACE2 ectodomain interaction. 124 We characterized the stability, dynamic range, and sensitivity of this biosensor and further showed that it could be used to identify inhibitors of the protein–protein interaction as recombinant RBD and ACE2 could be used as competitive inhibitors to block the interaction and decrease signal intensity. In developing a second biosensor for detecting SARS-CoV-2–host cell binding, we foresee a potential application for the RBD-ACE2 biosensor and S1 domain–ACE2 biosensors to be used in parallel as controls for each other and to investigate specific aspects of this protein–protein interaction.…”
Section: Roles For Luciferase-based Biosensors In the Study Of Sars-cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than examining RBD–ACE2 binding, this biosensor specifically interrogates the spike S1 domain and ACE2 ectodomain interaction. 124 We characterized the stability, dynamic range, and sensitivity of this biosensor and further showed that it could be used to identify inhibitors of the protein–protein interaction as recombinant RBD and ACE2 could be used as competitive inhibitors to block the interaction and decrease signal intensity. In developing a second biosensor for detecting SARS-CoV-2–host cell binding, we foresee a potential application for the RBD-ACE2 biosensor and S1 domain–ACE2 biosensors to be used in parallel as controls for each other and to investigate specific aspects of this protein–protein interaction.…”
Section: Roles For Luciferase-based Biosensors In the Study Of Sars-cov-2mentioning
confidence: 99%
“…Right: Outline of the NanoBiT split luciferase assay for Spike S1 and ACE2 binding upon addition of substrate furimazine. Adapted with permission from ref ( 124 ). Copyright 2021 Elsevier B.V.…”
Section: Roles For Luciferase-based Biosensors In the Study Of Sars-cov-2mentioning
confidence: 99%
“…To achieve this goal, we focused on antibodies that interfere with RBD:ACE-2 interactions as a proxy for antibody neutralization 12,13 ( Fig 1a ). We adapted a designed coronavirus spike RBD biosensor 14 consisting of a switchable lucCageRBD protein containing a “cage” domain that in the closed state of the sensor binds a “latch” domain containing the picomolar affinity RBD binding LCB1 protein, and a lucKey protein that binds to the open state of the sensor, reconstituting luciferase activity 14 .…”
Section: Mainmentioning
confidence: 99%
“…Unlike previously described competition assays which directly assess the extent of ACE-2:RBD complex formation (by luciferase reconstitution 12 or capturing of enzyme conjugated to one component 13 ) ( Fig 1c ), in this thermodynamic coupling scheme, the RBD is unmodified and free in solution. This simplifies testing reactivity against RBD variants of concern, since no labeling is required.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation